Re-Emergence of Necrotic Enteritis in the Broiler Industry - Shane, Simon M. (International Journal of Poultry Science, 2005)
Clostridial enterotoxemia occurs in the clinical forms of necrotic enteritis, cholangiohepatitis, and botulism. Broiler and turkey flocks which are fed diets devoid of antibiotic supplements with activity against Gram positive intestinal flora are susceptible to these conditions which detract from optimal productivity and yield. Factors which predispose to clostridial enterotoxemia include incorporation of more than 10% wheat or barley in diets, acute changes in the form or composition of diets, starvation or climatic and environmental stress including saturation of litter. Mild intestinal coccidiosis may frequently precipitate outbreaks of necrotic enteritis. Antibiotic dietary supplements including bacitracin, virginiamycin and lincomycin will effectively suppress proliferation of toxigenic clostridia when incorporated at sanctioned levels. Alternatives to antibiotics include commercial suspensions of `beneficial` bacteria including Lactobacillus spp. Bifidobacterium spp and Pediococcus spp. These are administered to chicks or poults in drinking water after placement or as a coarse spray after transfer to delivery boxes at the hatchery. Additional preventive measures include acidification of water and feed for newly placed flocks and incorporation of oligosaccharides and enzymes in diets. Supportive modalities comprise management of ventilation to maintain litter moisture between 20% and 25%, effective vaccination to prevent immunosuppressive infections (IBD, MD, CA) and control of coccidiosis.